A NOVEL POLYMORPHISM OF THE CYP4F2 GENE IS ASSOCIATED WITH ACUTE CORONARY SYNDROME. (8th October 2012) - Yang, Hong; Fu, Zhenyan; Ma, Yitong; Ma, Yitong
Abstract : Objectives: CYP4F2 is responsible for metabolising arachidonic acid to 20-hydroxyeicosatetraenoic acid (20-HETE), which plays a crucial role in the regulation of cardiovascular homeostasis. The present study aimed to evaluate whether or not the CYP4F2 gene polymorphism is involved in acute coronary syndrome (ACS). Methods: Four CYP4F2 SNPs were genotyped (rs1558139, rs3093166, rs3093194, rs2108622) using the Real-Time PCR System. We examined the role of these SNPs for ACS using two independent case–control studies: one was in the Han population (326 ACS patients and 338 control subjects) and the other was in the Uygur population (265 ACS patients and 276 control subjects). Results: CC+CT carriers of SNP4 (rs2108622) genotype were more frequent among ACS patients than among controls not only in the Han population of men (97% vs 91%) but also in the Uygur population of men (95% vs 88%).After adjustment of confounding factors such as smoking, alcohol consumption, hypertension, diabetes, body mass index, the OR for carriers of the rs2108622 genotype for ACS was 4.180 (95% CI 1.304 to 13.400) in the Han population of men and 2.878 (95% CI 1.059 to 7.825) in the Uygur population of men. Conclusions: The rs2108622 genotype of CYP4F2 may be a genetic maker of ACS in the Han and Uygur population of men in western China.